The Relationship Between Stress Levels, Learning Motivation, and Academic Performance of Nursing Students in Hybrid Learning at Universitas Muhammadiyah Kalimantan Timur - Budiman, Arief; Ashari, Maajid Surya Putra; Ghifari, Muhmmad Nurshandy Al; Burhanto, Burhanto (INDOGENIUS, 2025)
Background and Objective: This study aims to analyze the relationship between stress levels, learning motivation, and academic performance among nursing students in the hybrid learning environment. Method: This research uses a cross-sectional approach. The population of this study consists of 413 nursing students from the Universitas Muhammadiyah Kalimantan Timur for the academic year 2024/2025. The sampling technique used was simple random sampling, with a total sample size of 203 respondents. Data analysis was conducted using the Chi-Square test, and the instruments used were the Kessler Psychological Distress Scale (K10) questionnaire, a learning motivation questionnaire, and the students' latest GPA as an indicator of academic performance. Results: The results show a significant relationship between stress levels, learning motivation, and academic performance, with a ρ-value of 0.000 < α (0.05), indicating a significant relationship between stress levels, learning motivation, and academic performance. Conclusion: This study concludes that stress levels and learning motivation significantly influence academic performance in hybrid learning environments. These findings highlight the importance of considering stress levels and learning motivation in improving student performance in hybrid learning settings.